2020
DOI: 10.1002/jcla.23206
|View full text |Cite
|
Sign up to set email alerts
|

High level of D‐dimer predicts ischemic stroke in patients with infective endocarditis

Abstract: Background: Ischemic stroke is one of the most prominent and serious neurological complications of infective endocarditis (IE). Our study was designed to evaluate the predictive value of higher level of plasma D-dimer on admission for the development of ischemic stroke in patients with IE. Methods:In this prospective study, a total of 173 consecutive patients with IE were recruited from January 2016 to December 2018. Plasma D-dimer and other clinical indexes of IE patients were measured after admission. The nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Among coagulation parameters, D-dimers have received the most interest, and their use in clinical practice is well established. Our results corroborate previous data suggesting a predictive value of D-dimers for the short-term prognosis of IE and the prediction of embolism [16,17,23,24] and septic embolic stroke [18]. Consistently, Meini et al recently found that very high levels of D-dimers signaled a worse in-hospital outcome in patients with acute, severe infections [13].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Among coagulation parameters, D-dimers have received the most interest, and their use in clinical practice is well established. Our results corroborate previous data suggesting a predictive value of D-dimers for the short-term prognosis of IE and the prediction of embolism [16,17,23,24] and septic embolic stroke [18]. Consistently, Meini et al recently found that very high levels of D-dimers signaled a worse in-hospital outcome in patients with acute, severe infections [13].…”
Section: Discussionsupporting
confidence: 92%
“…Turak and colleagues suggested that high D-dimers levels on admission could identify IE patients at increased risk for in-hospital mortality [16]. Lin et al found D-dimers as a prognostic factor of in-hospital adverse events and six-month mortality [17], while Xu et al found that higher plasma D-dimers levels were predictive of ischemic stroke in 173 patients with IE [18]. However, use of coagulation markers in the prediction of IE prognosis has not yet entered into clinical practice [19].…”
Section: Introductionmentioning
confidence: 99%
“…An elevated DD level might be a meaningful predictor for embolism as a consequence of increased fibrin turnover. In a recent study, D‐dimer levels ≥3393 μg/L were significantly associated with the incidence of ischemic stroke in patients with IE 28 …”
Section: Predictors For Eementioning
confidence: 95%
“… DD > 3393 ng/dl for predicting ischemic stroke: sensitivity 78%, specificity 83%, area under the curve 0.856, 95% CI 0.77–0.92; p < .001 28 …”
Section: Predictors For Eementioning
confidence: 98%
“…Associated factors include co-morbidities like hypertension, diabetes or prior cerebrovascular disease (Moshayedi et al 2020). Biochemical factors like elevated C-reactive protein and elevated D-dimer also result in stroke among patients suffering from severe SARS-CoV-2 infection (Yaghi et al 2020;Tsushima et al 2020;Xu et al 2020b;Sato et al 2020;Reddy et al 2020).…”
Section: Cerebrovascular Disease and Strokementioning
confidence: 99%